Italian adolescents' adjustment before and during the coronavirus disease 2019: A comparison between mothers' and adolescents' perception. (29th September 2021) - Babore, Alessandra; Morelli, Mara; Trumello, Carmen
Abstract : The current cross‐sectional study aimed to analyse adolescents' adjustment during and before the lockdown caused by the coronavirus disease 2019 pandemic, by evaluating levels of emotional problems and hyperactivity as referred by adolescents themselves. A further purpose was to compare adolescents' and mothers' perception about adolescents' adjustment. Participants comprised 206 adolescents (50.5% females; mean age = 12.2; SD = 3.3) and their mothers (mean age = 43.9; SD = 5.9). Findings showed that levels of emotional symptoms and hyperactivity in adolescents during the pandemic were significantly higher than before. This worsening was consistently detected by both mothers and adolescents themselves. Two main conclusions are highlighted by the current research: During the first wave of the COVID‐19 pandemic, adolescents participating to this study detected a worsening in their well‐being; mothers' perceptions of their adolescents' psychological problems may be considered reliable and consistent with the offspring's point of view. Practitioner points: Italian adolescents' adjustment during the COVID‐19 outbreak has been little investigated. The current study highlighted a worsening in adolescents' well‐being, in terms of higher emotional symptoms and hyperactivity, with respect to the pre‐pandemic period. This worsening was consistently highlighted by both adolescents themselves and their mothers.